(untitled) (Informatica, 2025)
To address the serious waste of resources in high-rise buildings during the urbanization process, weak green awareness among construction personnel (only 42.3% theoretical accuracy), and rendering delays (102.7ms) and management virtualization in BIM technology applications, this study proposes a three in one solution of "technology management evaluation": the technical layer adopts an improved Hermite interpolation algorithm to achieve dynamic rendering of internal and external components separation, and the frame rate is increased to 58.7 FPS (compared to the optimal baseline+16.7%). The management team has built a digital platform that integrates VR training, sensor networks, and ontology reasoning. After testing and verifying with 200 workers, the training effectiveness has been improved by 112% (with a post training accuracy rate of 89.7%), and the material waste rate has been reduced by 69% (to 7.3%). The improved cloud model introduced by DPSIR framework in the evaluation layer reduced the evaluation bias rate to 4.7% (61.8% lower than fuzzy logic). The experiment shows that the framework significantly improves rendering efficiency (with only 1.2GB of memory usage), management collaboration (with a decision accuracy of 92.4%), and evaluation objectivity (expert consistency Kappa=0.82), forming a reusable green construction full chain optimization paradigm for high-rise residential buildings and overcoming the three major bottlenecks of delay, virtualization, and subjectivity.